AB0967 Ultrasonographic Features of Neuropathic (Charcot) Arthropathy of Ankle Joint. (15th July 2016) - Mortada, M.; Hammad, M.A.H.; Ezzeldin, N.
Abstract : Background: neuropathic osteoarthropathy (Charcot arthropathy) is a progressive condition that is characterized by joint dislocations, pathologic fractures, and debilitating deformities. It occurs most commonly in the lower extremity, at the foot and ankle. Although magnetic resonance imaging (MRI) is the modality of choice to examine patients with suspected neuropathic osteoarthropathy, for its ability to depict bone and soft tissues changes, ultrasonography (US) may be able to identify pathological changes in cases of Charcot arthropathy. Up to the best of our knowledge this the first study of ultrasonographic feature of neuropathic ankle joint. Objectives: Our aim was to characterize the ultrasonographic features of patients with neuropathic (Charcot) arthropathy of ankle joint. Methods: In this retrospective study, all 26 patients between January 2013 and December 2015 with neuropathic (Charcot) arthropathy of ankle joint proved by X ray and/or MRI were enrolled. We collected and analyzed 26 patients, on whom high-resolution (5–15 MHz) muculoskeletal US of ankle and small joints of the affected feet had been carried out. Results: Ages of our patients ranged from 38 to 67years (57.3± 6.4). Most of our patients (25 patients) 96.2% had diabetes mellitus and all of our patients had peripheral neuropathy. According to the modified Eichenholtz classification system; 3 patients (11.5%) were in grade 0, 11 patients (42.3%) were in grade 1, 10 patients (38.5%) were in grade 2, and 2 patients (7.7%) were in grade 3. Ultrasonographic findings were: Effusion/synovitis of ankle joints (100%), High Doppler activity (grade 2 or 3) in ankle joint was present in 92.3% of our patients, bone irregularities in distal fibula 73.1%, bone irregularities in distal tibia were found in 34.6%, tendonitis of tibialis posterior 65.4%, proneal tendonitis were found in 50%. Double contour sign were present in 2 ankle joints (7.7%). Arthritis (effusion/synovitis) in mid tarsal joints were found in 92.3% of patients with high Doppler activity in 65.4% and bone irregularities in57.7%. Conclusions: The main US features of neuropathic (Charcot) arthropathy of ankle joint are: effusion, synovitis, high grade Doppler activity, bone irregularities of the distal fibula and involvement of mid tarsal joints (synovitis, high Doppler activity and bone irregularities). Disclosure of Interest: None declared